Shared intentional engagement through language and phenomenal experience - Durt, Christoph (Frontiers in Psychology, 2014)
This article introduces the notion of shared intentional engagement and argues that the current debate around intersubjective interaction can profit from considering that notion. Shared intentional engagement is the engagement people are in when they intentionally relate to meaningful entities. For instance, when people talk about something, they share intentional engagment as long as they don’t talk past each other. But what if the entity talked about involves perceptual experience? It seems like the quality of someone’s experience is independent of language. Against the common assumption of a dichotomy between language and phenomenal experience, this article considers philosophical arguments for how language and phenomenal experience come together in shared intentional engagement, which matches well with empirical research on what I call “‘pop out’ experiences.” Because shared intentional engagement is fundamental for all kinds of human interaction, it necessitates interdisciplinary investigations that had been hindered by the assumption that phenomenal experience is independent of language.